Optimal Technique for Introducing Schwann Cells Into Peripheral Nerve Repair Sites - Errante, Emily L.; Diaz, Anthony; Smartz, Taylor; Khan, Aisha; Silvera, Risset; Brooks, Adriana E.; Lee, Yee-Shuan; Burks, S. Shelby; Levi, Allan D. (Frontiers in Cellular Neuroscience, 2022)
Peripheral nerve injury (PNI) is found in a relatively large portion of trauma patients. If injury is severe, such as with the presence of a long segmental gap, PNI can present a challenge for treatment. The current clinical standard of nerve harvest for repair of long segmental gap PNI can lead to many potential complications. While other methods have been utilized, recent evidence indicates the relevance of cell therapies, particularly through the use of Schwann cells, for the treatment of PNI. Schwann cells (SCs) are integral in the regeneration and restoration of function following PNI. SCs are able to dedifferentiate and proliferate, remove myelin and axonal debris, and are supportive in axonal regeneration. Our laboratory has demonstrated that SCs are effective in the treatment of severe PNI when axon guidance channels are utilized. However, in order for this treatment to be effective, optimal techniques for cellular placement must be used. Thus, here we provide relevant background information, preclinical, and clinical evidence for our method in the treatment of severe PNI through the use of SCs and axon guidance channels.